Diversity of barley yellow dwarf-associated viruses in winter cereals of Southern Sweden - Johnson, Marcelle Lauren (2019)
Barley yellow dwarf virus (BYDV) is a widespread complex of virus species of cereal crops in the world, known to infect both wild and cultivated plants of the family Poaceae, having the effect of yield reductions and subsequently large economic losses to farmers. Barley yellow dwarf disease (BYD) is a result of infection from BYDV species (genus: Luteovirus) and cereal yellow dwarf virus (CYDV; genus: Polerovirus). The symptoms of infection include the yellowing of leaf tips, rolling of leaf margins, stunting of plants, reduction in seed set and fertility. Taxonomically the viruses causing disease are the luteovirus species BYDV-MAV, BYDV-PAV and BYDV-PAS as well as the polerovirus CYDV-RPV. These are positive sense single-stranded RNA (+ssRNA) viruses vectored by different aphid species, including Sitobion avenae, Rhopalosiphum padi, Schizaphis graminun and Metopolphium dirhodum in a circulative nonpropagative manner. In Sweden, seasonal field surveys are conducted along with monitoring of aphid species to determine seasonal outbreak scenarios. In spring 2015 and 2017, BYD was confirmed from preliminary field surveys, identifying BYDV-PAV, BYDV-MAV and CYDV-RPV. This study was carried out to determine the viral diversity of isolates collected from plant material in southern Sweden, as well as to investigate the possible presence of phenotypic mixing or transcapsidation during infection in winter barley (Hordeum vulgare), winter wheat (Triticum aestivum) and winter rye (Secale cereale). DAS-ELISA and PCR amplification of the BYDV coat protein (CP) genes was used to determine viral diversity and the presence of phenotypic mixing or transcapsidation. Through sequence analyses of cloned PCR products, BYDV-PAV and BYDV-PAS were identified as viruses causing disease during outbreaks in spring 2015 and 2017. The BYDV-PAV isolates were closely related to previously recorded isolates of BYDV-PAV in Sweden, Latvia and Germany. In a phylogenetic analysis, Swedish and global BYDV-PAS isolates formed a well-supported group indicating that BYDV-PAS is a widespread virus. In addition, an isolate of Barley virus G, a virus first identified in barley of South Korea was identified in Swedish barley from the disease outbreak of 2015 and represents the first record of the virus in Sweden. DAS-ELISA results identified BYDV-PAV, BYDV-MAV and CYDV-RPV as viruses causing BYD disease in the outbreaks of 2015 and 2017, differing from that of CP gene sequence analysis which did not identify BYDV-MAV or CYDV-RPV. The results suggest that antibodies for BYDV-PAV and BYDV-MAV detect the CP of BYDV-PAS, because samples were most often positive for both BYDV-PAV and BYDV-MAV in DAS-ELISA, but BYDV-PAV and BYDV-PAS were detected by sequence analyses of the CP gene. Antibodies for CYDV-RPV seem to detect Barley virus G because of unspecific detection by DAS-ELISA antibodies for BYDV-PAV and BYDV-MAV, unable to adequately differentiate the CPs of these species. Future work should focus on ELISA antibody development for discrete identification of BYD virus species.